England hath need of thee: the omniscient narrator of Bleak House and Charles Dickens's Miltonic ascendance to cultural icon - Davidson, Laura Elizabeth (2017)
As a proponent for social change few authorrs have had the continuing impact or critical influence of Charles Dickens (1812-70), who used his writings to critique and, he wished, to change his culture. In this respect, Dickens was similar to John Milton (1608-74), who also attempted to shape the identity and values of his early modern culture through his literary endeavor. While Milton’s influence on Dickens can be seen in many of his novels, few scholars have directly addressed the Miltonic elements that Dickens implements in his writing. This thesis examines Dickens’s novel Bleak House (1852-53), and more specifically its omniscient narrator as a Miltonically-inspired voice used to narrate this complex story and what can be described as its prophetic message about the possibility of revolutionary disintegration in the midst of a drastically changing era.</DISS_para> <DISS_para>In this thesis, I explore, what I call, the prophetic message running throughout Bleak House and the three different personas that the omniscient narrator adopts to convey his prophetic message. I argue that the omniscient narrator becomes a type of muse for the reader—similar to the ways Milton invokes his Muse in Paradise Lost—in an attempt to help them better understand the novel’s prophecy through the use of direct references to Milton’s Paradise Lost. I also address Dickens’s use of passages from the Book of Common Prayer throughout the novel. Through these passages, the omniscient narrator becomes an intercessory figure for readers calling their attention to familiar prayerful language. I argue that the narrator’s prayers inspire readers to recite prayers over the novel’s characters and further emphasizes the plight of real people in Victorian London similar to the characters in Bleak House. The narrator’s third persona, the revolutionary historian, is perhaps the most crucial to better understand the revolutionary prophetic warning threaded through Bleak House. Essentially, the omniscient narrator refers to historical revolutionary action and reminds readers of the national and international consequences of revolution.</DISS_para> <DISS_para>This intertextual study, conducted through the lens of New Historical criticism, illuminates the way that Dickens implemented his ascent as a literary icon in response to Milton through the medium of the omniscient narrator. This study offers insight into the significant ways that Dickens utilized Milton in order to achieve a similar identity as a culturally defining and transformative priest and prophet especially through his novel’s omniscient narrator. Essentially, the omniscient narrator can be seen as a defining figure for Bleak House, and his three characteristics combined into one figure add to the novel’s impactful message and its ability to connect with its readers. Dickens answers his Romantic predecessor William Wordsworth’s call for another Milton who will bring England back to her national essence of “manners, virtue, freedom, power.”